Introduction of Face Image as Identifier of Using in Principal Component Analysis Method (PCA) - Wawan Krisdiyanto; Ika Irwanto; Lepi Astra Yudiansyah; Suhendro Yusuf Irianto (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Face recognition is a person identification system that uses a person’s facial characteristics. Facial recognition is itself a branch of biometrics, which is a science that uses physical characteristics of a person to determine or disclose his identity. The system developed in this thesis is a system that uses face recognition feature extraction based on Principal Component Analysis (PCA). This technique involves taking a major component of facial database. To determine the accuracy of human face recognition system designed in this final project, has conducted trials using the system with as many as 60 input facial image of the database. From the results of testing this system, the result is a 80% system performance in recognizing the input image correctly.Keywords : Facial Recognition, biometrik, PCA.